Paternal violent criminality and preterm birth: a Swedish national cohort study - Can Liu; Niklas Långström; Cecilia Ekéus; Thomas Frisell; Sven Cnattingius; Anders Hjern (BMC, 2020)
Abstract Background Fathers may affect expectant mothers' daily living situations, which in turn might influence pregnancy outcomes. We investigated the association between paternal violent criminality and risk of preterm birth (≤36 weeks). Methods We conducted a register-based study with all live singleton births in the Swedish Medical Birth Register from 1992 to 2012, linked with records of paternal violent crime convictions from the National Crime Register from 1973 to 2012. Results Paternal violent criminality was associated with increased risk of preterm birth and lower gestational age. The association was especially pronounced among infants of reoffenders: men convicted of three or more violent crimes (adjusted odds ratio [aOR] 1.23 [95% CI 1.17, 1.29]). Maternal half sibling-comparisons, an analytic approach controlling for maternal factors stable across pregnancies, also suggested increased risk of preterm birth and lower gestational age when exposed to a violently reoffending father compared to a father without violent criminal convictions (aOR 1.30 [0.99, 1.72], adjusted mean difference − 1.07 [− 1.78, − 0.36]). Conclusions Persistent paternal violent criminality was associated with increased risk of preterm birth, even after controlling for maternal characteristics that did not change between pregnancies.